Exploring barriers and facilitators in implementation fidelity of malaria screening intervention at Nepal-India border point-of-entry health desks-A mixed method study - Aney Rijal; E. Elsa Herdiana Murhandarwati; Megha Raj Banjara; Dilasha KC; Gokarna Dahal; Ari Probandari (PLoS ONE, 2025)
Purpose This research aimed to identify the barriers and facilitators in implementation fidelity of malaria screening at Nepal-India border Point of Entry (POE) health desks. Method A mixed-method approach was used guided by an implementation fidelity framework. Epidemiological records of reported malaria cases at selected border posts of Sudurpaschim and Lumbini province were obtained, while observation of the malaria screening was done among them. Qualitative inquiries were done with the health workers working at selected POEs, health coordinators and development partners working at respective districts, including representatives from three tiers of government: local municipalities, provincial and federal government. The suspected and confirmed migrant population were also interviewed about their experience while seeking for screening facility provided at POEs. Descriptive and trend analysis was done for number of tests per month and total malaria cases identified at POEs, while thematic analysis was performed for qualitative data. Results There were fluctuating testing trends from March 2021 to December 2022, where malaria screening was peaked before and after rainy season and during festivities and showed its the decreased priorities with the decreasing COVID-19 cases. Over those two consecutive years, 10 malaria cases were identified at POE in two provinces. Adherence to the screening protocol was partially followed, as there were limited guidance for malaria testing protocols at POE, incomplete fulfillment of health declaration forms, non-compliance in providing counseling during testing. Reported unavailability of test kits, variation in eligibility criteria, porosity of border, inadequate health workers, inaccessible infrastructures, limited awareness activities, fear of losing belongings among migrants, and administrative barriers were hindering the screening process. In contrast, presence of well-equipped infrastructures, perceived risk among the migrant’s population and regular monitoring during the monthly review meetings at the local health institutions facilitated the health workers for conducting screening. Conclusion The study concluded that prioritizing malaria detection and addressing barriers to ensure fidelity of malaria screening intervention is crucial.